1996
DOI: 10.1111/j.1911-3846.1996.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Auditor Changes and Reporting Lags*

Abstract: This paper examines audit report lags and eamings announcement lags for a sample of firms that switched auditors. We investigate whether audit report and earnings announcement lags are associated with the timing of auditor changes in relation to firms' fiscal year-ends. It is hypothesized that firms which replace their auditor early (late) in the fiscal year do so for positive (negative) reasons and experience shorter (longer) reporting lags. Conflicts over reporting issues can be difficult to resolve and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
135
2
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 21 publications
14
135
2
8
Order By: Relevance
“…Studies have generally concluded that Big N and international accounting firms both provide timelier US financial reports (Schwartz & Soo, 1996;Impink et al, 2012;Schmidt & Wilkins, 2013). International accounting research has also provided evidence that the use of Big N auditors is associated with shorter ARL in Canada , Bangladesh (Imam, Ahmed & Khan, 2001), and Greece (Leventis et al, 2005).…”
Section: Audit Firm Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have generally concluded that Big N and international accounting firms both provide timelier US financial reports (Schwartz & Soo, 1996;Impink et al, 2012;Schmidt & Wilkins, 2013). International accounting research has also provided evidence that the use of Big N auditors is associated with shorter ARL in Canada , Bangladesh (Imam, Ahmed & Khan, 2001), and Greece (Leventis et al, 2005).…”
Section: Audit Firm Characteristicsmentioning
confidence: 99%
“…On the other hand, Lee et al (2009) and Dao and Pham (2014) both documented that longer audit tenures are associated with shorter ARL. A related stream of research has found that companies that change their public accounting firm during the year required more days to complete their financial statement audit (Schwartz & Soo, 1996;Henderson & Kaplan, 2000;Ettredge et al, 2006). However, Tanyi, Raghunandan and Barua (2010) provided a deeper insight into this relationship.…”
Section: Audit Firm Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect the number of segments (NUM), extraordinary items (EXTR), negative earnings (LOSS), and an auditor's opinion (OPIN) to be positively related with LAG (Ashton et al, 1987;Schwartz & Soo, 1996). In addition, we include three more factors expected to impact audit procedure: busy seasons (YEND), auditor type (BIG4), and firm size (SIZE).…”
Section: Audit Related Factormentioning
confidence: 99%
“…We do not predict for YEND and BIG4 because of mixed results in the literature. The directions of these variables vary depending on audit resources and audit procedure (Schwartz & Soo 1996). The variable of SIZE is expected to be negative because large firms have more resources and keep excellent internal controls which shortens audit process and thus announcement delay (Owusu-Ansah, 2000).…”
Section: Audit Related Factormentioning
confidence: 99%